Impact of the Presence of Chronic Total Occlusions on the Survival of Patients Treated with Coronary Artery Bypass Grafting - Albi Fagu; Joseph Kletzer; Franziska Marie Ernst; Laurin Micek; Stoyan Kondov; Maximilian Kreibich; Clarence Pingpoh; Matthias Siepe; Martin Czerny; Tim Berger (Journal of Cardiovascular Development and Disease, 2025)
Although chronic total occlusions (CTO) are a common finding in patients treated with coronary artery bypass grafting (CABG), it is still not clear how their presence impacts the long-term outcomes achieved with surgery. We aimed to investigate the impact of CTO on the long-term results of patients with coronary artery disease who underwent CABG. Patients from 2005 to 2023 operated on at the University Hospital Freiburg-Bad Krozingen were analyzed. The primary outcome was all-cause mortality after 3-, 5-, and 10 years. The secondary outcome was the need for coronary reintervention in the follow-up period. Propensity score matching and multivariable Cox regression were performed, and Kaplan–Meier curves were used to graphically display the outcomes for the two groups. Of the 3424 patients included in the analysis, 1784 (52%) were categorized as CTO and 1640 (48%) were categorized as no-CTO. After propensity scoring, 1232 pairs were successfully matched. The 3-, 5-, and 10-year all-cause mortality was significantly higher in patients with CTO (p = 0.028; p < 0.001; p < 0.001). The need for coronary reintervention after 3-, 5-, and 10 years was comparable in both groups. In addition, multivariable Cox Regression showed that CTO presence (HR 1.220, 95% CI 1.047–1.420, p = 0.010) was an independent predictor of 10-year mortality.